lncRNA H19 acts as a ceRNA to regulate the expression of CTGF by targeting miR-19b in polycystic ovary syndrome - Sun,Xiuhong (2020)
The etiology of polycystic ovary syndrome (PCOS) is complex and the pathogenesis is not fully understood. Some studies have shown that dysregulation of ovarian granulosa cells may be related to abnormal follicles and excessive androgen in women with PCOS. Our team has also confirmed the high expression status of H19 in PCOS patients in the early stage. However, the relationship between H19 and miR-19b in the development of PCOS is still unknown. Therefore, we used bioinformatics to predict the binding sites of human H19 and miR-19b, and of miR-19b and CTGF genes. After the silencing and overexpression of H19, real-time polymerase chain reaction (PCR) was used to detect the expressions of H19, miR-19b, and CTGF. Western blotting was used to detect CTGF protein. Proliferation of KGN cells after H19 silencing was detected by CCK8. Flow cytometry was used to detect the apoptosis of KGN cells after H19 silencing. After the overexpression of H19, it was found that the expression of miR-19b gene decreased and the expression of CTGF increased, whereas silencing of H19 did the opposite. In addition, H19 could promote cell proliferation and decrease cell apoptosis. Finally, luciferase reporter assays showed that the 3′-end sequences of lncRNA H19 and CTGF contained the binding site of miR-19b. In conclusion, our study indicated that lncRNA H19 acted as a ceRNA to bind to miR-19b via a “sponge” to regulate the effect of CTGF on KGN cells, which may play a vital role in PCOS.